2020
DOI: 10.1371/journal.pone.0230564
|View full text |Cite
|
Sign up to set email alerts
|

Small-area variation  of cardiovascular diseases and select risk factors and their association to household and area poverty in South Africa: Capturing emerging trends in South Africa to better target local level interventions

Abstract: Background Of the total 56 million deaths worldwide during 2012, 38 million (68%) were due to noncommunicable diseases (NCDs), particularly cardiovascular diseases (17.5 million deaths) cancers (8.2 million) which represents46.2% and 21.7% of NCD deaths, respectively). Nearly 80 percent of the global CVD deaths occur in low-and middle-income countries. Some of the major CVDs such as ischemic heart disease (IHD) and stroke and CVD risk conditions, namely, hypertension and dyslipidaemia share common modifiable r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
(55 reference statements)
0
6
0
Order By: Relevance
“…To our knowledge, only one other study has assessed the relationship between this measure of area-level deprivation with cardiovascular health outcomes. In that analysis, which used data from SANHANES-1, area-level deprivation was positively associated with the prevalence of ischemic heart disease, but not hypertension [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To our knowledge, only one other study has assessed the relationship between this measure of area-level deprivation with cardiovascular health outcomes. In that analysis, which used data from SANHANES-1, area-level deprivation was positively associated with the prevalence of ischemic heart disease, but not hypertension [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SAMPI has been linked in prior research to various dimensions of health, including self-rated health and cardiovascular disease [ 42 , 43 ]. It has typically been modeled as a categorical variable with cut points based on the quintiles of the distribution of scores.…”
Section: Methodsmentioning
confidence: 99%
“…Amadi et al (2018) reported a nearly three times increased odds of hypertension in those who were overweight/obese. Data from SANHANES also found that hypertension was highest for those who were overweight (48.3%; N = 16,293) [ 36 ]. A recent study on CVD risk factors in long-distance bus drivers in Lagos, Nigeria (N = 293), reported that BMI and an extended length of time as a professional driver correlated with the risk of hypertension [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marked racial stratification developed during the Apartheid era in South Africa placed Whites at the top, Indians and Coloureds in the middle, and Africans at the bottom [38]. Geographic location was categorized as formal urban, informal urban, formal rural, or informal rural [39][40][41][42]. Age was categorized into 10-year groups.…”
Section: Variablesmentioning
confidence: 99%